No ordinary duchess - Hoyt, Elizabeth, 1970- (Hoyt, Elizabeth, 1970- Greycourt novel., 2024)
"Cold and brooding, Julian Greycourt, the heir to the Windemere dukedom, has always known that his uncle the duke was responsible for his mother's death. Now he's determined to exact revenge against his uncle--if he can find the proof. But Julian hides a secret so explosive it will destroy him if it's ever revealed, and the duke is watching. The last thing he needs is a distractingly sensual woman whose very presence threatens to destroy his plans. Sunny and cheerful, Lady Elspeth de Moray doesn't know why her brother and Julian fell out all those years ago, but she can't let the autocratic man get in the way of her mission: to retrieve an ancient family text that she believes is in one of the Windemere libraries. Locating the tome, however, proves trickier than she anticipated, and at each turn, she's thrown together with the maddingly mysterious Julian. And the temptation to give in to her family's greatest enemy grows stronger with each intriguing encounter..."--Back cover.